INITIATING ESP WRITING THROUGH PHOTOVOICE: A QUALITATIVE CASE STUDY OF INDONESIAN UNDERGRADUATE MANAGEMENT STUDENTS - Dita Adawiyah; Amirul Mukminin; Urip Sulistiyo (University of Kuningan, 2026)
Starting to write is often the most challenging stage for students in English for Specific Purposes (ESP), particularly in English as a Foreign Language (EFL) contexts. Few studies, however, have examined how students initiate writing rather than focusing on the final product, leaving a gap in understanding the emotional and cognitive processes involved in writing initiation. This study addresses this gap by exploring how Photovoice supports students in beginning ESP writing. A qualitative case study was conducted with 15 undergraduate students from a Management Study Program at a private Islamic university in South Sumatra. Data were collected from students’ written texts, reflective responses, and semi-structured interviews, and analyzed thematically. The findings indicate that Photovoice provides a concrete starting point for writing, helping students generate ideas from familiar daily-life contexts and reducing hesitation when facing a blank page. Participants reported feeling more emotionally prepared and confident, and Photovoice also facilitated early draft organization, allowing a natural progression from description to reflection and connections with management-related topics. The study contributes to ESP writing pedagogy by demonstrating that multimodal, experience-based approaches like Photovoice can enhance students’ engagement and support the initiation phase of writing in EFL higher education contexts.